Effect of braced excavation on tunnels in clay - Wong, Teck Hong. (2011)
Braced excavation construction adjacent to a tunnel may cause damages to the tunnel during the excavation process. Damages to the tunnel could be caused by basal heave failure due to excavation, excessive tunnel movement and excessive bending moment induced during excavation. The purpose of this report is to investigate the impact of nearby braced excavation construction on various tunnel design configurations in soft clay. The aspects that are examined are displacement and bending moment of tunnel. Various design configurations such as depth of tunnel, wall embedment depth, wall stiffness, distance of tunnel from excavation are varied to study their effect on the displacements and bending moments of the tunnel. The results show that a stiffer wall can reduce both displacements and bending moments of the tunnel. However, its extent of improvement can be affected and restricted by the embedment depth of wall. The results show that an increase in embedment depth of wall yields significant improvement to performance of tunnel only if the wall is sufficiently stiff.